GIBBERELLIC ACID PRIMING ENHANCES MAIZE SEED GERMINATION UNDER LOW WATER POTENTIAL - Amit Gnawali; Roshan Subedi (Indonesian Agency for Agricultural Research and Development, 2021)
Germination is a portentous yield determining factor that is a challenge in the low water potential environment due to disrupted imbibition. Hormonal seed priming can markedly increase the germination on maize even in such a stressful environment. Therefore, research was aimed to analyze the application of gibberellic acid (GA3) priming to maize seeds to minimize the deleterious effects of reduced water potential. GA3 priming was done at 0, 50, 100, 150, and 200 ppm for 12 hours and subjected to drought levels of 0, 0.15, 0.50, 1.05, and 1.75 MPa by using NaCl solution. Different germination parameters, i.e., germination percentage, mean germination time, germination index, relative water content, seedling vigor index, root length, and shoot length, were determined on the final day of the experiment. The results showed that all germination parameters were adversely influenced by low water potential. Every level of GA3 priming has hastened all parameters. GA3 priming at 100 ppm decreased the mean germination time by 35 hours under 1.75 MPa compared to non-primed seeds. GA3 priming increased the shoot length of maize seedlings with a shoot length of 2.9 cm in non-primed seedlings compared to 6.4 cm in 200 ppm GA3 priming under 1.05 MPa. GA3 priming is the best method for the early establishment of maize seedlings in low water potential conditions. As a result, it may be utilized as a low-cost and straightforward approach for establishing maize crops under saline and drought conditions.